Augmented Reality Portal 360 Degrees Tourism “Bundaran Balanga” Sampit - Minarni Minarni; Fery Setiawanto; Linda Norhan; Tedi Kustandi (Institute of Computer Science (IOCS), 2021)
The tragedy that occurred in the Sampit area 20 years ago was commemorated and immortalized by the local government with the construction of the